Average Capacity Evaluation Performance for Transdermal Optical Wireless Communications under the Effect of Pointing Error - Hasan, Omar Musa (International Journal of Online and Biomedical Engineering (iJOE), 2022)
In this paper, we investigate the performance of average capacity of transdermal wireless optical communication system under the effect of pointing error and skin attenuation. The channel statistical model is assumed to be the product of a stochastic process due to pointing error, and a constant channel gain caused by the skin attenuation. Furthermore, the transdermal optical wireless system employs intensity modulation direct detection with on-off signaling (IMDD/OOK), and the pointing error stochastic process only considers the zero boresight case. We derive novel closed form expression for the average capacity which takes into account the effect of geometric spreading due to pointing error, and the transdermal channel pathloss. Numerical results for the average capacity are provided as a function of the received signal-to-noise ratio, and the results are shown for different pointing error severity levels, and transdermal pathloss due to skin attenuation